Remote Hind-Limb Ischemia Mechanism of Preserved Ejection Fraction During Heart Failure - Homme, Rubens P.; Zheng, Yuting; Smolenkova, Irina; Singh, Mahavir; Tyagi, Suresh C. (Frontiers in Physiology, 2021)
During acute heart failure (HF), remote ischemic conditioning (RIC) has proven to be beneficial, however; it is unclear whether it also extends benefit from chronic congestive; cardio-pulmonary heart failure (CHF). Previous studies from our laboratory have shown three phases describing CHF viz. 1: HF with preserved ejection fraction (HFpEF), 2: HF with reduced EF (HFrEF), and 3: HF with reversed EF. Although reciprocal organ interaction, ablation of sympathetic and calcium signaling genes are associated with HFpEF to HFrEF the mechanism is unclear. The HFrEF ensues, in part, due to reduced angiogenesis, coronary reserve and leakage of endocardial endothelial (EE), and finally breakdown of blood heart barrier (BHB) integrity. Our hypothesis states that a change in phenotype from compensatory HFpEF to de-compensatory HFrEF, in fact, is determined by a potential decrease in regenerative and proangiogenic factors along with a concomitant increase in epigenetic memory and inflammation that combinedly cause oxidative and proteolytic stress response. To test this hypothesis, we created CHF by aorta-vena-cava (AV) fistula in a group of mice that were subsequently treated with that of hind-limb remote ischemic conditioning (RIC). HFpEF versus HFrEF transition was determined by serial/longitudinal echo measurements. Results revealed an increase in skeletal muscle musclin contents, bone-marrow (CD71), and sympathetic activation (β2-AR) by RIC. We also observed a decrease in vascular density and attenuation of EE-BHB function due to a corresponding increase in the activity of MMP-2, VEGF, caspase and the calpain. This decrease was successfully mitigated by RIC-released skeletal muscle exosomes that contain musclin; the myokine along with bone marrow and sympathetic activation. In short, based on proteome (omics) analysis of ~20 proteins that appear to be involved in signaling pathways responsible for the synthesis, contraction, and relaxation of cardiac muscle, were found to be the dominant features. Thus, our results support that CHF phenotype causes dysfunction of cardiac metabolism, its contraction and relaxation. Interestingly, RIC was able to mitigate many deleterious changes, as revealed by the multi-omics findings.